A pharmacogenetics approach to pain management - Kaori Yoshida; Daisuke Nishizawa; Soichiro Ide; Tatsuya Ichinohe; Ken‐ichi Fukuda; Kazutaka Ikeda (Wiley, 2018)
Abstract Introduction Opioid analgesics are widely used as effective analgesics for the treatment of moderate‐to‐severe pain. However, the analgesic efficacy of opioids is well known to vary widely among individuals, and effective pain treatment is hampered by vast individual differences. Although these differences in opioid requirements have been attributed to various factors, genetic factors are becoming increasingly relevant to the development of genome science. Aim This review covers the association between opioid analgesic requirements and particularly gene polymorphisms. Future perspectives Personalized pain treatment has begun using prediction formulas based on associated gene polymorphisms. Improvements in personalized pain treatment are expected as scientific knowledge further expands in the future.